Challenges in Implementing Differentiated Learning in English Classes: Teachers’ and Students’ Perspectives - Rini, Tasya Yanti; Patanduk, Sushy Teko; Sallata, Yizrel Nani (Jurnal Studi Guru dan Pembelajaran, 2023)
This study investigates the challenges faced by English teachers in implementing differentiated learning and explores students’ perceptions toward this approach in class XI at SMAN 5 Tana Toraja. Using a qualitative method, data were gathered through classroom observations and interviews with English teachers. The findings reveal that while differentiated strategies, such as group learning, multimedia, and task variations, improve student engagement and comfort, several barriers persist. These include time constraints, large class sizes, and diverse student abilities. Nonetheless, both teachers and students acknowledged the benefits of adapting teaching styles to meet students’ varied needs. The study recommends continuous innovation and teacher support to enhance Differentiated learningin English language classrooms